NINATI SEDANG ‘MERIAS’ DIRI: SEBUAH KAJIAN PEMBERDAYAAN MASYARAKAT ADAT - Susanti, Antik Tri; Wijanarka, Tunjung (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
In the present-day era, the notion of human development is a key concept that has been continuously pursued by various nations, including Indonesia. Nonetheless, there are still numerous regions and communities in the outermost, foremost, and disadvantaged areas that have yet to fully experience the benefits of development. To support the process of human development, it is crucial to establish a synergistic collaboration across multiple sectors, involving not only the government but also the private sector, academia, and the local community. The Muyu tribe, residing in Ninati Village, Ninati District, Boven Digoel Regency, South Papua, represents an indigenous community situated on the brder between Indonesia and Papua New Guinea (PNG) that is currently making strides towards enhancing human development. In response to this pressing need, academics from Universitas Kristen Satya Wacana (UKSW) and several other stakeholders have taken the initiative to empower the indigenous people of Muyu tribe. Though on-site research and remote empowerment process, the involvement of UKSW academics and other parties aims to facilitate empowerment and foster various aspects of human development by harnessing the indigenous people inherit potential.